(3JgPjH GdceGd aj CSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s ((3eMeO Hf ScQ GdOjQi GdTGaYi s)
(3ChdgG (B:s
(3jfbU TjFkG jSjQkG ef GdebOeI , hChd GdehLhO efg (B: (3hdcf GdfGS eNJdahf ai Pdc ENJdGakG cKjQkG s
(3BNQgG (B:s
(3aGHJOQg GdfGS aGSJNQLhG efg GdZU QhGg CHh OGhO hgh MOjK MSf YRjR s
(3fbdJ ef fSNI GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs